CD22 and Siglec-G in B cell function and tolerance - Poe, Jonathan C. (2012)
The immune system has evolved into two main arms, the primitive innate arm that is the first line of defense but relatively short-lived and broad acting, and the advanced adaptive arm that generates immunologic “memory” allowing rapid, specific recall responses. T cell-independent type-2 (TI-2) antigens (Ags) invoke innate immune responses. However, due to its “at the ready” nature, how the innate arm of the immune system maintains tolerance to potentially abundant host TI-2 Ags remains elusive. Therefore, it is important to define the mechanisms that establish innate immune tolerance. This review highlights recent insights into B cell tolerance to theoretical self TI-2 Ags, and examines how the B cell-restricted Siglecs, CD22 and Siglec-G, might contribute to this process.